Sources and Distribution of Mercury Residues in Environmental and Food Matrices of the Mekrou River Watershed in Kèrou, Kouandé and Péhunco in Republic of Benin - YOUSSAO ABDOU KARIM, ALASSANE; DAOUDA, Mahamadou; ALASSANE MOUSSA, Abdoul Kader; MAMA, DAOUDA; YOUSSAO ABDOU KARIM, ISSAKA (My University, 2018)
Environmental scientific research has been largely developed for about a century, and many disciplines have been interested in interactions and the role of hazardous chemical elements such as metallic mercury and its inorganic and organic compounds in the environment. This study aims to assess the mercury contamination level of some foodstuffs (water, milk) and of the terrestrial and aquatic environment (fodder, agricultural soil and sediments) in the municipalities of 2KP. Total mercury (T-Hg) has been determined by DMA-80 (Direct Mercury Analyzer) in different environmental and food matrices of the Mekrou river watershed in Kèrou, Kouandé and Péhunco (2KP municipalities). The mercury content is higher in the superficial horizon of agricultural soil (0-20 cm) than in the horizon (20-40 cm). Watercourses (Mekrou River and its tributaries) have relatively low levels of Hg (0.5 to 1.3 μg/L) in water compared with ponds and dams (181.2 to 616.9 μg/L). Conversely, ponds and dams are characterized by low levels of mercury in water and relatively higher levels in sediments. Concentrations of Hg in cow's milk and cattle feed varied respectively in the concentration ranges of (0.4 to 8.7 μg/L) and (7.1 to 15.7 μg/kg). Regarding plant material, the highest concentrations of mercury (15.7 μg/kg) are obtained in the okra leaves (Abelmsehus eseuilleus (L.) Moench) used in the human diet, ompared to cattle fodder. This work reveals agriculture as the leading source of mercury ecosystem contamination, followed by Artisanal and Small-Scale Gold Exploitation (ASSGE) and hospital sources in 2KP municipalities.
Keywords: DMA-80; Pollution with Hg; Anthropogenic Sources; Kérou; Kouandé; Péhunco